Analisa AB-Mix Dan Air Cucian Beras Pada Pertumbuhan Tanaman Selada (Lactuca Sativa, L.) Dengan Wick System Hidroponik - Simatupang, Ulina; M. Samosir, Osten; Alfizar, Rizky (Fakultas Pertanian Universitas Winaya Mukti, 2024)
AB mix nutrition consists of two different packages, the elements contained in it are macro (N, P, K, Mg, Ca, S) and micro (Fe, Zn, Mo, Cu, Mn, Bo, Cl, Si, Na, Co). Rice washing water contains nitrogen, phosphorus, carbohydrates, sulfur, magnesium, potassium, vitamin B1 and iron. The results showed that the treatment dose of rice washing water had a significant effect on plant height, number of leaves and root weight. The higher the dose of rice washing water, 30 ml/water, the higher the plant growth will be. The results of research on the interaction of AB mix treatment with rice washing water had no significant effect on plant height, leaf color and root weight in lettuce plants. Keywords :AB mix , Hydroponics, Rice Washing Water and Wick System